Emerging trends in blacksmithing in Benin City, Nigeria - Kingsley Osevwiyo Emeriewen (Journal of Science and Technology of the Arts, 2015)
Blacksmithing in Benin City, Nigeria is of significant antiquity. The popularity and importance of the practice in the city is reinforced in the blacksmiths guild's attachment to the palace of the Oba, the traditional ruler of Benin people and their kingdom. This study examined the shift in paradigms and emerging trends in the practice. Based on the study of the blacksmiths and their products over a period of fourteen years, the study determined how the blacksmiths have responded to modern challenges. Findings indicate that a good number of the blacksmiths are multi-skilled in metal working and that they work with metals, other than iron, and employ modern tools and methodologies which were originally not traditional to blacksmithing.  The study also classified the blacksmiths’ products, most of which were also not traditional to their craft, into five categories: household utensils, farming implements, musical instruments, religious artefacts and decorative objects.